La création scénique galicienne du XXIe siècle face à l’histoire et à la mémoire - Fabrice Corrons (Cahiers de Civilisation Espagnole Contemporaine)
This article questions the presence of historical material in the scenic creation of Galicia in the 21st century. It first offers a quick study of this relationship to the past in the Galician theater of previous centuries. The central part is devoted to the representation of the period 1931-1975 (Second Republic, Civil War and Franco’s dictatorship) since 2001 and to the question of memory in the present time. Finally, the contribution makes an analysis of the shows on previous or later historical facts of the central period (1931-75).